Răspuns :
[tex]\frac{1}{2}=1-\frac{1}{2}[/tex]
[tex]\frac{2}{3} =1-\frac{1}{3}[/tex]
[tex]\frac{3}{4} =1-\frac{1}{4}[/tex]
...
[tex]\frac{99}{100}=1-\frac{1}{100}[/tex]
Notam:
[tex]S=\frac{1}{2}+\frac{2}{3} +\frac{3}{4}+...+\frac{99}{100}[/tex]
[tex]S=1-\frac{1}{2}+1-\frac{1}{3}+1-\frac{1}{4}+...+1-\frac{1}{100}[/tex]
Avem 99 de 1
[tex]S=99-(\frac{1}{2} +\frac{1}{3} +...+\frac{1}{100})[/tex]
Calculam [tex]x=\frac{1}{2} +\frac{1}{3}+...+\frac{1}{100}[/tex]
Stim ca:
[tex]\frac{1}{(n+1)(n+2)} =\frac{1}{n+1} -\frac{1}{n+2}[/tex]
[tex]\[ \sum_{i=1}^{99} \frac{1}{n+1} \][/tex]=[tex]\frac{1}{2}+\frac{1}{3}+...+\frac{1}{100}[/tex]
[tex]\[ \sum_{i=1}^{99} \frac{1}{n+2} \][/tex]=[tex]\frac{1}{3}+\frac{1}{4}+...+\frac{1}{100}+\frac{1}{101}[/tex]
[tex]\[ \sum_{i=1}^{99} \frac{1}{(n+1)(n+2)} \]=[/tex][tex]\[ \sum_{i=1}^{99} \frac{1}{n+1} \]-[/tex][tex]\[ \sum_{i=1}^{99} \frac{1}{n+2} \][/tex]
[tex]\[ \sum_{i=1}^{99} \frac{1}{(n+1)(n+2)} \]=[/tex][tex]\frac{1}{2} -\frac{1}{101} =\frac{99}{202}[/tex]
[tex]x=\frac{99}{202}[/tex]
[tex]S=99-\frac{99}{202} =\frac{99\times201}{202}[/tex]
Deci rezultatul nostru va fi:
[tex]\frac{99\times201}{202}\times(\frac{17}{51}-\frac{19}{57} )=\\\\\frac{99\times201}{202}\times (\frac{1}{3}-\frac{1}{3})= \frac{99\times201}{202}\times 0=0[/tex]